STUDI KELAYAKAN SIFAT – SIFAT AGREGAT UNTUK CAMPURAN BETON TERHADAP NILAI KUAT TEKAN BETON DI PROYEK REKONSTRUKSI ATAU PENINGKATAN KAPASITAS STRUKTUR JALAN KADUT – SP. GUNUNGLARANG TONGGOH KEC. BANTARUJEG KAB. MAJALENGKA - Suson Rudianto, Encep; Rijaluddin, Arief (SEMINAR TEKNOLOGI MAJALENGKA (STIMA), 2023)
This study aims to analyze the aggregate properties for concrete mixtures on the compressive strength of concrete and compare the aggregate material between quarry Ex. Cikeruh (which is used in the project), quarry Ex. Cideres, and quarry Ex. Cilutung. Tests carried out in accordance with SNI and Bina Marga specifications. The results of testing in the laboratory were obtained. From the three quarry, all of them were suitable for use as mixed concrete materials because they met the specifications required by SNI and Bina Marga. Judging from the results of the concrete compressive strength test, the quality plan fc'20 28 days old, Mixed Quarry Ex. Cideres has a higher compressive strength value so it gets a quality yield of 24.34 MPa while Quarry Ex. Cikeruh obtained 22.08 Mpa, and Quarry Ex. Cilutung gets 20.38 Mpa.